2009
DOI: 10.1007/s12640-009-9103-4
|View full text |Cite
|
Sign up to set email alerts
|

6-Hydroxydopamine Lesions in the Rat Neostriatum Impair Sequential Learning in a Serial Reaction Time Task

Abstract: Sequential behavior has been intensively investigated in humans using so-called serial reaction time tasks(SRTT), in which visual stimuli are either presented in a random or sequential order. Typically, when the stimulus presentation follows a previously learned sequential order,reaction times are decreased compared to random stimulus presentation and become partly automated. A vast amount of SRTT findings indicates that sequential learning and performance seem to be mediated amongst others by the basal gangli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
(36 reference statements)
2
13
0
Order By: Relevance
“…Referring to a previous experiment which revealed that sequential learning as assessed by our rat SRTT is severely affected by dopaminergic lesions in the neostriatum (Eckart et al, 2010a), our results strongly support the hypotheses of a possible interference between striatum and hippocampus in some test situations, as previously proposed by and Packard and Knowlton (2002). Both models assume that interference between both structures may occur during striatal stimulus-response learning and hippocampal spatial learning.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Referring to a previous experiment which revealed that sequential learning as assessed by our rat SRTT is severely affected by dopaminergic lesions in the neostriatum (Eckart et al, 2010a), our results strongly support the hypotheses of a possible interference between striatum and hippocampus in some test situations, as previously proposed by and Packard and Knowlton (2002). Both models assume that interference between both structures may occur during striatal stimulus-response learning and hippocampal spatial learning.…”
Section: Discussionsupporting
confidence: 91%
“…In case of omissions and incorrect pokes, feedback was provided by a tone and illumination of the house light. Then, stimulus presentation continued from that item, where the sequence had been interrupted (Eckart et al, 2010a). Schematic design for the object place recognition test.…”
Section: Basic Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…8c-f ). Although the caveats detailed above prevent us from drawing strong conclusions about DA's role in vocal learning other than that driven by white noise, future studies could ask whether DA is necessary for error-corrective learning by providing a correctable auditory perturbation to baseline song without explicit external reinforcement (Sober and Brainard, 2009;Hoffmann et al, 2012). Prior studies have identified potential mechanisms by which dopaminergic inputs to area X might mediate vocal learning.…”
Section: Discussionmentioning
confidence: 99%
“…As in a number of forms of mammalian behavioral plasticity (Ogura et al, 2005;Eckart et al, 2010), the basal ganglia are crucial for vocal plasticity in songbirds. Area X (Fig.…”
Section: Introductionmentioning
confidence: 99%